RAD1 and RAD10, but not other excision repair genes, are required for double-strand break-induced recombination in Saccharomyces cerevisiae. - Ivanov, E L (1995)
HO endonuclease-induced double-strand breaks (DSBs) in the yeast Saccharomyces cerevisiae can be repaired by the process of gap repair or, alternatively, by single-strand annealing if the site of the break is flanked by directly repeated homologous sequences. We have shown previously (J. Fishman-Lobell and J. E. Haber, Science 258:480-484, 1992) that during the repair of an HO-induced DSB, the excision repair gene RAD1 is needed to remove regions of nonhomology from the DSB ends. In this report, we present evidence that among nine genes involved in nucleotide excision repair, only RAD1 and RAD10 are required for removal of nonhomologous sequences from the DSB ends. rad1 delta and rad10 delta mutants displayed a 20-fold reduction in the ability to execute both gap repair and single-strand annealing pathways of HO-induced recombination. Mutations in RAD2, RAD3, and RAD14 reduced HO-induced recombination by about twofold. We also show that RAD7 and RAD16, which are required to remove UV photodamage from the silent HML, locus, are not required for MAT switching with HML or HMR as a donor. Our results provide a molecular basis for understanding the role of yeast nucleotide excision repair gene and their human homologs in DSB-induced recombination and repair.